Unveiling the importance of controllable growth of c-axis oriented Sn-doped ZnO nanorod arrays: Towards humidity sensing applications - Ahmad Syakirin, Ismail @ Rosdi; Mohamad Hafiz, Mamat; Ruziana, Mohamed; Embong, Z.; Kossar, Shahnaz (Elsevier Ltd, 2025)
In this study, tin (Sn)-doped zinc oxide (ZnO) nanorod arrays (SZO) were prepared using a sonication assisted sol-gel immersion method, with the growth of the nanorod arrays controlled by varying the immersion time in the precursor material. Morphology images taken using a Field Emission Scanning Electron Microscope (FESEM) demonstrated an enlargement of the average diameter of the nanorod arrays from 55 nm at 5 min immersion to 122 nm at 200 min immersion. The cross-sectional and surface elemental analysis showed that the sample immersed for 60 min has the highest detection of Sn, with a bulk concentration of 1.8 at.% and surface concentration of 1 at.%. Interestingly, we noticed that Sn is not exist on the surface of 200 min immersion, indicating the depletion of the Sn precursor due to the prolongation of the immersion time. From the current voltage (I-V) analysis, 60 min immersion sample generated the lowest thin film resistivity, which engendered the best humidity sensitivity of 4.05. This study demonstrated the significant importance of optimizing the immersion or growth time for doped 1-D nanostructures to obtain the best humidity sensing performance.